Assessment of the influence of stakeholders in the development of Lithuanian airports - Gelžinis, Marius; Jarašūnienė, Aldona (Business: Theory and Practice, 2024)
Air transport is the only way to reach Lithuania from abroad in the short and medium term. Despite a well-developed road network in the country, connections to other European capitals are long and inconvenient. 2014 July. Vilnius, Kaunas and Palanga airports were merged into one state-owned company, Lithuanian Airports (LTOU). Since then, the efficiency and overall profitability of LTOU operations have increased significantly. However, maintaining the airport’s current infrastructure is costly and needs upgrading and further investment. The company has repeatedly asked itself whether it can get more benefits by building one new Lithuanian airport or focusing on developing the existing three airports net. Stakeholders’ views and recommendations should be heard to make timely and appropriate decisions without a new airport’s technical and financial feasibility. An in-depth interview and secondary data analysis were selected for the empirical study. Thirteen employees of SE Lithuanian Airports and three of the Ministry of Transport and Communications of the Republic of Lithuania participated in the research. The following was used to analyse secondary data: SE Lithuanian Airport strategic plan, the material of strategic sessions, and a survey of the country’s population on the need for a new airport. The study found that stakeholders positively assess the long-term development projects of SE Lithuanian Airports, fully understanding the importance of airports and their contribution to the welfare of the state. Stakeholders can significantly impact results, so airport managers must consider whether they effectively involve stakeholders and, if not, how they can improve or encourage stakeholder involvement.